2007
DOI: 10.1007/s10554-007-9240-x
|View full text |Cite
|
Sign up to set email alerts
|

Accessory appendages of the left atrium as seen during 64-slice coronary CT angiography

Abstract: Accessory left atrial appendages were visualized in 10% of 166 patients during 64-slice coronary CT angiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…Our findings do not show any association between diverticula and CVA or TIA. Consistent with several prior studies, our image analysis did not show evidence of thrombi within accessory appendages, diverticula or septal pouches [6] [7] [9] [12]. Nevertheless, given the high prevalence of LAAA, consideration of evaluation for thrombi within LAAA prior to electrophysiologic procedures may be useful for clinical management and risk reduction.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings do not show any association between diverticula and CVA or TIA. Consistent with several prior studies, our image analysis did not show evidence of thrombi within accessory appendages, diverticula or septal pouches [6] [7] [9] [12]. Nevertheless, given the high prevalence of LAAA, consideration of evaluation for thrombi within LAAA prior to electrophysiologic procedures may be useful for clinical management and risk reduction.…”
Section: Discussionsupporting
confidence: 88%
“…Smooth and communicating diverticula are suggested to create a potential "loop" to trigger a transmission disorder (8,9,11,12). As coronary CTA is problematic in patients with disordered cardiac rhythms such as atrial fibrillation (13), these patients were excluded from our study, and thus the relationship between atrial fibrillation and the frequency of atrial diverticula could not be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…1 Recently, accessory appendages of the LA have been described with a prevalence of between 10% and 28%. 2 The majority are located along the anterior LA wall adjacent to the ostium of the right superior PV. Histopathological analysis of such accessory appendages has shown that they contain trabeculated myocardium with the same wall structure as the surrounding myocardium.…”
mentioning
confidence: 99%